Surrogate marker for predicting the virus binding of urogenital cancer cells during adenovirus-based gene therapy - Yun-Jun Lai; Rey-Chen Pong; John D. McConnell; Jer-Tsong Hsieh (BioTechniques, 2003)
Virus uptake is the first rate-limiting step for the successful gene delivery of any virus-based gene therapy. For adenovirus-based gene therapy, the expression levels of the adenovirus receptor—coxsackievirus and adenovirus receptor (CAR)—play an important role in dictating gene delivery. We have observed a wide spectrum of CAR expression among cancer cell lines and tumor specimens. Therefore, the screening of the CAR expression level in patients becomes crucial for any possible positive outcome. In this paper, we establish a real-time RT-PCR assay for the detection of CAR mRNA levels from cancer cells and tumor specimens. This assay appears to be very quantitative, with sample concentrations ranging within 6 logs, and the sensitivity of this assay could detect as low as 1.8 × 102 copies of CAR cDNA per reaction. The results from this assay confirmed that there was a good linear relationship between the CAR mRNA and virus binding from each cell line. With this assay, we were able to detect changes in CAR gene expression in cells treated with histone deacetylase inhibitor. Most importantly, CAR mRNA levels directly correlated with its protein levels prepared from tumor specimens. Taken together, this assay could provide a rapid screening tool for any adenovirus-based gene therapy trial.